Perlindungan Hukum Hak Kekayaan Intelektual Bagi Produk Kreatif UMKM di Jawa Timur - Bayani, Kania Nurul; Santoso, Budi (Universitas Ekasakti, 2024)
This research aims to analyze the legal protection provided to creative products of Micro, Small, and Medium Enterprises (MSMEs) in East Java in the context of intellectual property rights (IPR). With rapid economic growth, MSMEs have become one of the main pillars driving regional economic growth. However, the challenges faced by MSMEs lie in protecting their creative products from piracy and violations of intellectual property rights. Through a qualitative approach, this study will analyze the legal framework governing IPR for MSMEs in East Java, including relevant laws, regulations, and government policies. The research will also identify the challenges and obstacles faced by MSMEs in obtaining IPR protection, as well as efforts made by the government and related institutions to increase awareness of the importance of IPR protection for MSMEs. The findings of this research are expected to provide a better understanding of IPR protection for MSMEs in East Java and offer policy recommendations to enhance the effectiveness of IPR protection and support the growth and development of MSMEs in the region.